2019
DOI: 10.1063/1.5053572
|View full text |Cite
|
Sign up to set email alerts
|

Oblique propagation of longitudinal spin-electron acoustic waves under the influence of the Coulomb exchange interaction and the quantum Bohm potential

Abstract: Influence of the exchange interaction on the properties of the spin-electron acoustic waves at the oblique propagation of waves relatively to the external magnetic field in the magnetically ordered metals is studied. The spectra of the Langmuir wave and the Trivelpiece-Gould wave are also considered. It is well-known that there are two branches of spectrum of the spin-electron acoustic waves in this regime. Change their properties under influence of the exchange interaction is studied. The quantum Bohm potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…[32][33][34][35][36] The combined effect of the exchange interaction and Bohm potential on the frequency spectra of obliquely propagating electrostatic waves has been studied, and it has been concluded that these effects have an opposite effect on the phase velocity of the waves. [37] Recently, the existence of new spin-dependent transverse waves in the spectra of obliquely propagating extraordinary waves has been reported in refs [21,38]. The SSE-QHD model has been used to study the electrostatic beam-driven instabilities in bounded [39] and unbounded [40] electron-ion plasma.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34][35][36] The combined effect of the exchange interaction and Bohm potential on the frequency spectra of obliquely propagating electrostatic waves has been studied, and it has been concluded that these effects have an opposite effect on the phase velocity of the waves. [37] Recently, the existence of new spin-dependent transverse waves in the spectra of obliquely propagating extraordinary waves has been reported in refs [21,38]. The SSE-QHD model has been used to study the electrostatic beam-driven instabilities in bounded [39] and unbounded [40] electron-ion plasma.…”
Section: Introductionmentioning
confidence: 99%